Taxonomic, functional, and phylogenetic perspectives on butterfly spatial assembly in northern Amazonia - GraÇa, MÁrlon Breno (Ecological Entomology, 2020)
1. Understanding the causes of the spatial variation of biodiversity is an important goal in community ecology. This study investigated the response of fruit-feeding butterfly assemblages to environmental gradients resulting from the transition from ombrophilous forests to white-sand forests in northern Brazil by assessing taxonomic, functional and phylogenetic descriptors of community structure. 2. Butterflies were sampled with bait traps in the Brazilian Amazon, while their traits and phylogenetic relatedness were either measured directly or gathered from the literature. Then, the effects of plant species turnover, light intensity, and flood risk on butterfly community patterns were tested. 3. Butterfly abundance increased with light intensity in non-forested white-sand habitats, whereas ombrophilous forests harboured higher species richness. A trade-off was observed between richness and abundance across the gradient. Plant turnover strongly drove shifts in butterfly species composition. In white-sand habitats, butterflies had higher dispersal capacity, faster flights and generalist larvae, whereas in periodically flooded plots the functional diversity of flight-related traits was higher. No phylogenetic response to environmental gradients was detected. 4. These results exposed the complexity of community structure across a mosaic landscape and how analysing more than one dimension of biodiversity may reveal underlying relationships not apparent under isolated approaches. Caution is required when using phylogeny as a proxy for functional similarity, as the responses were not congruent in this study. The ecological patterns revealed here, aligned with further regional-scale studies, can provide complementary perspectives on butterfly spatial distribution and ensure that appropriate conservation policies are developed. © 2017 The Royal Entomological Society